1995
DOI: 10.3354/meps120211
|View full text |Cite
|
Sign up to set email alerts
|

Memorization of heavy metals by scales of the seagrass Posidonia oceanica, collected in the NW Mediterranean

Abstract: Concentrations of Cd, Cu, Fe, Pb and Zn were measured in scales of the seagrass Posidonia oceanica from different areas of the French NW Mediterranean: the Cbte d'Azur and Corsica.Scales are basal parts of the seagrass which remain fixed on the rhizomes when leaves of P. oceanica die. Scales do not decay and the cyclic variation of their thickness permits retroactive dating (lepidochronology). Heavy metal concentrations were determined in the scales of P. oceanlca dated by lepidochronology. Scales from P. ocea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
31
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 16 publications
10
31
3
Order By: Relevance
“…Although an increasing trend in Cd has been reported as a worldwide phenomenon, because 99% of Cd in the atmosphere is due to anthropogenic emissions [31], no univocal trend was found for all the sites. Cadmium concentrations in scales were in the same range as in dated scale samples of the same period from northern Corsica and the Cote d'Azur [12]. Cadmium concentrations in scales were in the same range as in dated scale samples of the same period from northern Corsica and the Cote d'Azur [12].…”
Section: Cadmiumsupporting
confidence: 54%
See 1 more Smart Citation
“…Although an increasing trend in Cd has been reported as a worldwide phenomenon, because 99% of Cd in the atmosphere is due to anthropogenic emissions [31], no univocal trend was found for all the sites. Cadmium concentrations in scales were in the same range as in dated scale samples of the same period from northern Corsica and the Cote d'Azur [12]. Cadmium concentrations in scales were in the same range as in dated scale samples of the same period from northern Corsica and the Cote d'Azur [12].…”
Section: Cadmiumsupporting
confidence: 54%
“…Heavy metals are significant environmental contaminants of seagrass systems [4,[9][10][11][12]. Previous field studies of seagrasses have shown that several species accumulate an array of trace metals [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This is astonishing in the case of scales which are dead tissues constituted by the dead sheathes, remaining after the leaf decay. The 15 N measured in scales was probably passively absorbed during the labelling by the same mechanism involved as for Fe accumulation (Roméo et al, 1995). The 15 N abundance in scales does not show a clear temporal variation.…”
Section: Discussionmentioning
confidence: 78%
“…3 km) to the main sewer of Marseille (Delmas 1990). Although poorly documented on a quantitative basis, differences in the global metal contamination of the three meadows are supported by time-series investigations through analysis of the scales of P. oceanica (Pergent-Martini 1992;Roméo et al 1995).…”
Section: Samplings and Sample Preparationmentioning
confidence: 99%